Pembelajaran TOEFL sebagai Upaya Peningkatan Kompetensi Guru di MGMP Kabupaten Muara Enim - Hesti Wahyuni Anggraini; Zuraida Zuraida; Rita Hayati; Dwi Maharrani; Nova Lingga Pitaloka (Universitas Hamzanwadi, 2023)
In Indonesia, TOEFL (Test of English as a Foreign Language) learning has become crucial in enhancing English proficiency, particularly for English language teachers across various regions. Proficiency in the English language serves as a key factor in meeting educational quality standards. Therefore, TOEFL training has become a necessary endeavor to support teachers' English language mastery and elevate the quality of instruction in the pursuit of standardized schools. This community engagement aims to provide TOEFL training as an effort to enhance English language proficiency among English teachers in Kabupaten Muara Enim, South Sumatra. The training was conducted online via the Zoom Conference application, with a total of 77 teacher participants. The training curriculum encompassed fundamental TOEFL skills, including Listening, Structure and Written Expression, and Reading. The training process involved several stages, including pre-test assessments, presentations, discussions, mentoring, and post-test evaluations. The results of the training demonstrated a noticeable improvement in TOEFL scores among the teachers. The average initial TOEFL score was 426, with the lowest score at 286 and the highest at 536. After the training, the average final TOEFL score increased to 432, with the lowest score at 296 and the highest at 557. Although the score changes were not statistically significant, they indicate an enhancement in the understanding and English language proficiency of the participants. The training proved effective in elevating English language comprehension among English teachers in Kabupaten Muara Enim. The effective delivery of training materials and interactions with resource persons positively contributed to the teachers' English language proficiency. It is recommended to conduct follow-up activities to assess the application of acquired knowledge after the training. Such initiatives are expected to further enhance the positive impact of the training on the teachers' pedagogical practices. Moreover, similar training activities could be extended to a provincial level, involving a larger number of teachers, thus fostering improvements in the education sector within the region.